2017
DOI: 10.4081/ija.2017.1040
|View full text |Cite
|
Sign up to set email alerts
|

Germination and performance of seven native wildflowers in the Mediterranean landscape plantings

Abstract: The use of native species in landscape design is a choice related to environmental sustainability and it contributes to the aesthetic appeal of urban and marginal areas. However, to date, the lack of knowledge of the ecological characteristics and agronomic practices of these species, represents a limit for their use. This study aims to obtain information about germination ecology, morphological traits and ornamental value of 7 selected perennial native taxa, with potential use in meadows seed mixtures for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 30 publications
1
12
0
1
Order By: Relevance
“…Ideal cover-crop species should be native, with low requirements and low competitive ability. Studies targeted to identify cover crops suitable for hopyard management in the Mediterranean environment are lacking [101].…”
Section: Weed Controlmentioning
confidence: 99%
“…Ideal cover-crop species should be native, with low requirements and low competitive ability. Studies targeted to identify cover crops suitable for hopyard management in the Mediterranean environment are lacking [101].…”
Section: Weed Controlmentioning
confidence: 99%
“…Ona ovisi o jednostavnosti razmnožavanja i eventualnim problemima u tehnologiji proizvodnje, podnošenju različitih ekoloških uvjeta, otpornosti na bolesti i štetnike ali i samoj dekorativnosti vrste. Nedostatak znanja o ekološkim svojstvima i tehnologiji uzgoja samoniklih vrsta predstavlja limitirajući faktor za njihovu upotrebu (Scarici et al, 2017.). Kako bi se procijenio početni potencijal neke vrste za uvođenje u uzgoj potrebno je za početak sakupiti osnovne podatke o vrsti, njenoj rasprostranjenosti, ekologiji te prirodnoj varijabilnosti morfoloških svojstava što će omogućiti selekciju i daljnje razmnožavanje fenotipski superiornih jedinki.…”
Section: Uvodunclassified
“…The European Environment Agency [1] states that the 'quality of life in cities depends on the existence of sufficient attractive urban green areas for people and wildlife to thrive'. Recent research indicated that the biodiversity in green areas, both within and outside cities, should be increased by using native wildflowers [2][3][4]. These are defined as combinations of annual or perennial herbaceous wild species suitable for sowing in low maintenance areas [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%